Gravimetric and Electrochemical Methods to Evaluate the Performance of Corrosion Inhibitors for Galvanized Steel Strips - Monsalve-Gonzalez, A; Artigas-Abuin, A (Walter de Gruyter GmbH, 2018)
Corrosion inhibitors with Cr+6 and Cr+3 are applied on the surface of metals to increase their chemical resistance when they are exposed to severe degradation conditions. For galvanized low-carbon steel strip, these compounds are applied to reduce corrosion mainly during transport operations of this metal. The performance of corrosion inhibitors deposited on the surface of galvanized steel strip was evaluated through combined physical and electrochemical modeling. The physical model takes into account direct exposure of specimens to different conditions including simulated marine, industrial and rain environments for periods up to 8 weeks. The efficacy of the experimental method was also evaluated using polarization resistance and gravimetric means. A good correlation between the evolution of the degradation phenomenon obtained directly from the physical model and the electrochemical and gravimetric data was found. The results showed that this method is an effective tool that allows the comparison of the performance of different corrosion inhibitors that could be used to prevent surface degradation of galvanized steel strip. © 2018 Walter de Gruyter GmbH, Berlin/Boston 2018.